LA DOCUMENTATION AUTOMATIQUE EN DROIT ET LA REACTION DE LA PROFESSION JURIDIQUE/(DOCUMENT RETRIEVAL SYSTEMS IN LAW AND THE REACTION OF THE LEGAL PROFESSION) - Mackaay, Ejan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF